Modulation of CXC Chemokine Receptor Expression and Function in Human Neutrophils during Aging In Vitro Suggests a Role in Their Clearance from Circulation. (1st March 2009) - Weisel, Katja C.; Bautz, Frank; Seitz, Gabriele; Yildirim, Sedat; Kanz, Lothar; Möhle, Robert
Abstract : In mice, differential regulation of CXC chemokine receptor expression in circulating polymorphonuclear neutrophils (PMNs) undergoing senescence results in homing to the bone marrow. However, the role of this compartment and of the chemokine receptor CXCR4 is still under discussion, and only scarce data exist about CXCR4 function in human PMN. In our study, we provide evidence that also in human neutrophils, expression (cell surface and mRNA), chemotactic and signaling functions of the homing-related chemokine receptor CXCR4 are upregulated during aging in vitro, independent of addition of stimulatory cytokines (TNF, IL-1, IL-8, G-CSF). In contrast, interleukin-8 receptors are downmodulated (CXCR2) or remain unchanged (CXCR1), suggesting that human PMNs undergoing senescence acquire a phenotype that impairs inflammatory extravasation and favors homing to the bone marrow or other tissues involved in sequestration. Partially retained responsiveness to interleukin-8 may be important for neutrophil function when senescence occurs after extravasation in inflamed tissues.